INFLUENCE OF ALARM AND ANXIETY IS ON THE EMOTIONAL STATE OF SCHOOLBOY (Psychology Travelogs, 2023)
By analyzing the theory, using a variety of modern sources of information, the article examines the concept of anxiety and anxiety itself. It is shown that anxiety is just an emotion and it does not always carry something negative for a person. On the contrary, it mobilizes our body and protects us from possible danger. To call it positive, there are several key conditions. It is necessary that it is within the normal range, and that the anxiety caused by it is due to real threats. Then it helps us, in other cases it harms the general emotional state of a person. The article also discusses the concept of anxiety, which is an individual personality trait, i.e. it is a kind of emotional state accompanied by constant, excessive worries. It should also be noted that this publication draws attention to school anxiety, which is the interaction of a student with various components of the learning environment in which the child is. Such interaction is negative, it has a significant destructive effect on the psyche of a student who is just forming himself as a person. And this should be understood because not only adults have an increased level of anxiety, but also schoolchildren have difficulty coping with their own experiences. Due to the overall development of society, students are under increasing pressure from the information load, they are required to quickly master new technologies, information, ideas, and more. Adolescents not only need to cope with puberty, which carries with it rapid hormonal processes, frequent changes in emotions, and the experience of new feelings, but also to deal with the overwhelming anxiety that is present in their lives. And this negatively affects not only the level of education but also their formation as a person in society.  Adolescents can develop personal anxiety and interfere with their ability to live a normal, fulfilling life.
Keywords: alarm; anxiety; anxiety disorder; school anxiety